APPROACHES TO FORMING THE PROFESSIONAL CULTURE OF FUTURE TEACHERS - Sultonova O’g’ilkhon Sobirjonovna (Bright Mind Publishing, 2025)
This article presents some ideas on the approaches to forming the professional culture of future teachers, the priority of forming the image of a modern teacher, and the professional culture of a modern teacher. The article also presents ideas on the fact that the work of a teacher-educator on the formation of the spiritual and moral, in particular, pedagogical image of teachers is a complex and multifaceted process.
Keywords: Professional culture, approaches, modern teacher, spiritual and moral attitude, pedagogical image, educational process, development trends, pedagogical ability.